Organizational Commitment as a Mediator of Organizational Support and Emotional Intelligence in Shaping Organizational Citizenship Behavior - Junita, Audia; Hafas, Hafriz Rifki; Nasution, Muhammad Alwi Syahputra (Jurnal Manajemen Bisnis, 2022)
Research aims: This study aims to analyze the effect of organizational support and emotional intelligence on organizational citizenship behavior (OCB) through employee organizational commitment.Design/Methodology/Approach: This research was conducted in the Central Bureau of Statistics in Medan City with a population of 100 permanent partner employees. Using non-probability sampling, the entire population became the research sample. Meanwhile, the analysis technique employed path analysis.Research findings: The results proved that organizational support and emotional intelligence had a significant effect directly on organizational citizenship behavior (OCB) and indirectly through employees' organizational commitment. In other words, increased organizational support and emotional intelligence of employees will intensify the level of employee organizational commitment, raising the level of organizational citizenship behavior (OCB) and vice versa. In this case, organizational support strongly predicts employees’ high organizational commitment. Theoretical contribution/Originality: Further research that explores other predictors needs to be carried out with more significant respondents to generalize the findings better.Practitioner/Policy implication: It is essential to provide more intensive organizational support to employees since this variable is a strong organizational predictor of generating a superior level of employee organizational commitment. Organizations also need to conduct in-depth personality tests to detect the level of individual emotional intelligence of employees who work in the field and interact with the community for better work effectiveness.Research limitation/Implication: The limited number of population and samples in the agency is a limitation of the study to generalize the findings better.